2016
DOI: 10.5559/di.25.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Systems in Croatian Regions

Abstract: The goal of this paper was to research and apply the concept of Regional Innovation Systems (RIS) to Croatian regions and to identify particular strengths supporting innovation diffusion as a source of regional competitiveness. A system of indicators is envisaged, with the choice of RIS dimensions and indicators largely relying on Evangelista, Iammarino, Mastrostefano, and Silvani (2001). In total, 32 relevant regional indicators are grouped into three dimensions -Knowledge creation and dissemination, Firm inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Various initiatives have emerged due to the cooperation between different stakeholders within innovation system which relate to the development of innovation indicators. The most well-known source of information for measuring enterprise innovation performance (input/output-oriented indicators) is Community Innovation Survey (CIS) (Bačić and Aralica, 2016; Dziallas and Blind, 2019). CIS methodology, developed by the OECD and EUROSTAT, contributes to a better understanding of innovative behavior of companies by defining the indicators of innovative behavior which can determine the impact of innovation on employment, competitiveness, economic growth, forms of trade, etc.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Various initiatives have emerged due to the cooperation between different stakeholders within innovation system which relate to the development of innovation indicators. The most well-known source of information for measuring enterprise innovation performance (input/output-oriented indicators) is Community Innovation Survey (CIS) (Bačić and Aralica, 2016; Dziallas and Blind, 2019). CIS methodology, developed by the OECD and EUROSTAT, contributes to a better understanding of innovative behavior of companies by defining the indicators of innovative behavior which can determine the impact of innovation on employment, competitiveness, economic growth, forms of trade, etc.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The RIS concept combines the literature on innovation and the literature regarding the region. The innovation literature, from a system perspective, explains the innovation process as a result of the quality of interaction of "firms, universities, and research centers", while the literature regarding regional innovation can be observed in a spatial context, where the "socio-institutional environment and economic structure" enable knowledge creation and diffusion among the institutional actors [39].…”
Section: Literature Review 21 National Innovation System Regional mentioning
confidence: 99%
“…Counties are selected as the prime unit used in mapping and by using relevant indicators, counties are mapped into larger unitsregions that will be further analysed throughout the paper. As mentioned, findings from previous papers are acknowledged (Bačić, Aralica, 2016) in finding relevant criteria to purse the mapping procedure and determine the borders of regions and their centres -major cities that are cores of regional economic activity.…”
Section: Mapping Of Regions Based On Ris Conceptmentioning
confidence: 99%
“…Current focus of regional development policy are counties, but these units by definition do not meet RIS criteria. Furthermore, Bačić and Aralica (2016) find in their research of RIS in Croatia that that NUTS 2 level, which is used as a unit of comparison in cross-European regional competitiveness research, is not a "natural" regional economic unit to be considered when designing regional innovation policies and strategies in Croatia. In the context of S3RC, industrial and innovation policies, more obvious regional units emerge from firm and human resources agglomeration pattern and the pattern of technological-scientific infrastructure 4 .…”
Section: A) the Identification Of Regions Based On Ris Concept Acrossmentioning
confidence: 99%